"It's a chance to make mistakes": Processes and outcomes of coding in 2nd grade classrooms. (July 2021) - Egbert, Joy; Shahrokni, Seyed Abdollah; Abobaker, Reima; Borysenko, Nataliia
Abstract: Several gaps exist in the literature on coding. First, little exploration has focused on early elementary school students. In addition, close description of the overall context of coding tasks at this level is rare. Further, there is a need for both teacher and student voices around coding experiences to be heard. Moreover, a task engagement framework has not been used to evaluate the process or outcomes of early elementary coding tasks. Therefore, an exploratory holistic case study design was used to investigate student and teacher processes and outcomes of coding lessons in order to fill gaps in the literature. In this study, forty-six 2nd grade students, two teachers, and four researchers completed two one-week units on basic coding. Multiple descriptive and numeric data sources were employed to describe the process and outcomes of learning coding. Conclusions include: (1) teachers should start learning about coding first with short awareness sessions and then move to their own classrooms with knowledge brokers and other forms of assistance; (2) a focus on content and process, including problem-solving, is effective for coding with young children; (3) there can be a high level of engagement for teachers and students with the use of robots and welldesigned, age-appropriate coding tasks, and; (4) multiple data sources and the inclusion of both teacher and student data are essential in exploring coding in classrooms. Highlights: Two authentic classrooms of 2nd graders and their teachers. Use of multiple data sources. Focus on task engagement as an essential construct. Both teacher and student voices included.